2020
DOI: 10.1377/hlthaff.2020.01081
|View full text |Cite
|
Sign up to set email alerts
|

Racial/Ethnic Differences In COVID-19 Screening, Hospitalization, And Mortality In Southeast Wisconsin

Abstract: This study aims to understand racial/ethnic differences in coronavirus disease 2019 screening, symptom presentation, hospitalization, and mortality, using data from 31,549 adults tested for COVID-19 between March 1 and July 10, 2020, in Milwaukee and Southeast Wisconsin. Racial/ethnic differences existed in adults screening positive for COVID-19 (4.5 percent of non-Hispanic Whites, 14.9 percent of non-Hispanic Blacks, and 14.8 percent of Hispanics). After adjusting for demographics and comorbidities, minoriti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
35
1
3

Year Published

2021
2021
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 39 publications
(45 citation statements)
references
References 22 publications
(38 reference statements)
2
35
1
3
Order By: Relevance
“…Studies published since June 2020 tend to support our findings of disparities in COVID-19 infection, hospitalization, and mortality by race or ethnicity [88][89][90][91][92][93][94][95][96], socioeconomic status and deprivation [88-90, 92, 93, 97], and housing insecurity [95,96,98,99]. At least two recent studies did not find associations between race and mortality outcomes among those able to access hospital care [100,101], contrary to findings of most other research, including this review.…”
Section: Plos Onecontrasting
confidence: 51%
“…Studies published since June 2020 tend to support our findings of disparities in COVID-19 infection, hospitalization, and mortality by race or ethnicity [88][89][90][91][92][93][94][95][96], socioeconomic status and deprivation [88-90, 92, 93, 97], and housing insecurity [95,96,98,99]. At least two recent studies did not find associations between race and mortality outcomes among those able to access hospital care [100,101], contrary to findings of most other research, including this review.…”
Section: Plos Onecontrasting
confidence: 51%
“…Evidence suggests social risk factors such as low income and lack of access to care could explain some of this disparity [22]. Recently published studies have reported that African Americans are more likely to be tested for COVID-19 in the emergency department or inpatient settings and are more likely to be admitted to the hospital compared to non-Hispanic whites [23][24][25]. This is thought to reflect the lack of access to care and delay in seeking care due to lack of trust in the system which results in more advanced disease at the time of presentation [23].…”
Section: Discussionmentioning
confidence: 99%
“…Yet, not all findings are consistent; e.g., there was no racial disparity in COVID19 mortality rates among ZIP codes grouped by the proportion of Black residents in a nearby (affluent) county [31] . Clinical studies have also provided evidence that African Americans who seek hospital care are at increased risk of COVID19 mortality; however, the racial disparities appear to be explained by social factors or differences in comorbidities in most [ [8] , [9] , [10] , [11] ], but not all [ 7 , 12 ], reports.…”
Section: Discussionmentioning
confidence: 99%
“…Multiple studies of people able to access hospital care reported no Black-White people difference in COVID19 mortality risk after adjusting for sociodemographic factors and clinical comorbidities [ [8] , [9] , [10] , [11] ]. Yet, not all studies agree.…”
Section: Introductionmentioning
confidence: 99%